Guideline for privacy and security in Cloud First Security Environment - Abdul Aziz, Normaziah; Mansor, Hafizah; Mohd Nor, Rizal; Wahiddin, Mohamed Ridza (Cyber Security Center of Excellence, Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
This is a guideline for Cloud adopters to leverage on Cloud’s benefit while managing to avoid possible risks that may be encountered. The discussion of privacy and security in Cloud computing platform which includes data classification, security and privacy governance, guideline implementation and security cases brings a thorough understanding on Cloud and its policy.